Gender difference in the relationship between metabolic syndrome and vitamin D in Korean adults with obesity. - Yoon, Hyun; Sung, Hyun Ho; Gi, Mi Young; Cha, Ju Ae; Park, So Young; Park, Cho Hee; Kim, Sun Gyu; Han, Eun Sook (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: The present study was conducted to assess the relationship between metabolic syndrome (MetS) and serum 25-hydroxyvitamin D [25(OH)D] in Korean adults with or without obesity. Materials and Methods: The study was performed using data from the sixth Korean National Health and Nutrition Examination Survey (KNHANES VI, 2013-2014) and included Korean adults with or without obesity aged 20 years or older (n = 3,499). Results: The key results of this study were as follows: first, after adjusting for related variables, the relationship between MetS and the odds ratio (OR) of vitamin D deficiency [25(OH)D < 10 ng/mL] was not significant in men, premenopausal women, and postmenopausal women without obesity. Second, in premenopausal women with obesity, the relationship between MetS and vitamin D deficiency was not significant (OR, 1.241; 95% CI, 0.551–2.797; p = 0.603). However, MetS was positively associated with vitamin D deficiency in men (OR, 1.839; 95% CI, 1.038–3.258; p = 0.037) and postmenopausal women (OR, 3.136; 95% CI, 1.316–7.470; p = 0.010) with obesity. Conclusions: MetS was not associated with vitamin D deficiency in Korean men, and postmenopausal women without obesity. MetS was positively associated with vitamin D deficiency in Korean men and postmenopausal women with obesity but not in premenopausal women with obesity.